Brain-based Correlations Between Psychological Factors and Functional Dyspepsia - Nan, Jiaofen (J Neurogastroenterol Motil, 2015)
BACKGROUND/AIMS: Increasing evidence shows involvement of psychological disorders in functional dyspepsia (FD), but how psychological factors exert their influences upon FD remains largely unclear. The purpose of the present study was to explore the brain-based correlations of psychological factors and FD. METHODS: Based on Fluorine-18-deoxyglucose positron emission tomography-computed tomography, the altered cerebral glycometabolism was investigated in 40 FD patients compared with 20 healthy controls during resting state using statistical parametric mapping software. RESULTS: FD patients exhibited increased glucose metabolism in multiple regions relative to controls (P < 0.001, family-wise error corrected). After controlling for the dyspeptic symptoms, increased aberrations persisted within the insula, anterior cingulate cortex (ACC), middle cingulate cortex (MCC) and middle frontal cortex (midFC), which was related to anxiety and depression score. Interestingly, FD patients without anxiety/depression symptoms also showed increased glycometabolism within the insula, ACC, MCC and midFC. Moreover, FD patients with anxiety/depression symptoms exhibited more significant hypermetabolism within the above 4 sites compared with patients without anxiety/depression symptoms. CONCLUSIONS: Our results suggested that the altered cerebral glycometabolism may be in a vicious cycle of psychological vulnerabilities and increased gastrointestinal symptoms.